Composition for anti-crack glass, anti-crack glass as well as preparation method and application of anti-crack glass
By optimizing the component mass fraction in the composition for crack-resistant glass, the problem of insufficient anti-falling ability of existing glass products is solved, and the anti-falling height and anti-falling performance are significantly improved.
Patent Information
- Application Number
- CN202510086657.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-20
AI Technical Summary
Existing glass products are weak in resistance to impact (resistance to drop) of sharp objects and are prone to cracks and breakage when falling.
A composition for crack-resistant glass, including SiO2, Al2O3, Li2O, Na2O, K2O, MgO, Y2O3 and ZrO2, is used to improve the drop resistance and crack resistance of the glass by optimizing the mass fraction of these components.
The anti-crack glass has significantly improved the anti-fall height and anti-fall properties, ensuring that the glass can resist cracks and breakage more effectively when it falls.
Smart Images

Figure CN119797755A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of glass, and in particular to a composition for crack-resistant glass, crack-resistant glass, and a preparation method and application thereof. Background Art
[0002] Glass has always been an indispensable material in the development of display technology. Changing the composition of the glass surface through chemical strengthening can improve the strength of the glass, making glass more widely used in the protection of display devices.
[0003] At present, the cover glass used for screen protection of mobile phones, computers, smart watches and other mobile devices with touch screen panels is usually required to have excellent physical properties and high mechanical properties, such as high mechanical strength, high Young's modulus, high chemical temperature resistance and thinness, so that the mobile device can avoid screen damage caused by external factors such as impact, drop, scratch, and extrusion during use.
[0004] Studies have shown that 80% of mobile phone screens are broken due to accidental drops. Conventional chemically strengthened glass has a high level of resistance to flat object impact, but is generally weak in resistance to sharp object impact (anti-drop). For example, glass products are prone to cracks and even breakage when they fall from a height onto a rough surface (such as cement floor, gravel, sandpaper, etc.).
[0005] In the prior art, the drop and impact resistance of glass products is very limited. Therefore, how to provide a glass composition to improve the drop and crack resistance of glass products is still a problem that needs to be solved urgently. Summary of the invention
[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a composition for crack-resistant glass, crack-resistant glass and its preparation method and application. The crack-resistant glass prepared by the composition for crack-resistant glass of the present invention has high drop resistance and excellent anti-fall performance.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a composition for crack-resistant glass, wherein the composition for crack-resistant glass comprises SiO2, Al2O3, Li2O, Na2O, K2O, MgO, Y2O3 and ZrO2 in the form of oxides;
[0009] Taking the total mass of the composition for crack-resistant glass as 100wt%, the mass fraction of Al2O3 is 16wt%-21wt%, for example, it can be 16wt%, 17wt%, 18wt%, 19wt%, 20wt% or 21wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0010] In the present invention, Al2O3 is introduced to improve the strength of the glass structure. Non-bridging oxygen and Al form aluminum oxide tetrahedrons, which are larger in volume than silicon oxide tetrahedrons, and produce larger gaps in the glass structure, which is beneficial to ion exchange, and ultimately makes the chemical strengthening effect better, improving the scratch resistance and drop resistance of the glass. However, if the Al2O3 content is too high, it is difficult to melt; if the Al2O3 content is too low, the glass is easy to crystallize, and the mechanical strength is low, which is not conducive to molding. The content of Al2O3 in the present invention is 16wt%-21wt%.
[0011] Based on the total mass of the composition for crack resistant glass as 100wt%, the mass fraction of Li2O is 2wt%-6.5wt%, for example, it can be 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt% or 6.5wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0012] Based on the total mass of the composition for crack resistant glass as 100wt%, the mass fraction of Na2O is 0.5wt%-4wt%, for example, it can be 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt% or 4wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0013] Taking the total mass of the composition for crack-resistant glass as 100wt%, the mass fraction of K2O is 1wt%-4wt%, for example, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt% or 4wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] The Li2O, Na2O and K2O introduced in the present invention are the main exchange ions in the chemical strengthening process. + The ionic radius is larger than that of Na + Smaller, contains Li + The glass ion exchange rate is faster, so that the glass can obtain a thicker strengthening layer in a short time. + Ions and Na in the melt + Ion exchange, and faster than Na + With K +The exchange speed is fast. However, when the Li2O content is high, it will cause serious erosion to the refractory material. When the Na2O and K2O contents are high, the expansion coefficient of the glass will increase, the mechanical properties of the glass will be reduced, and the speed of chemical strengthening will be affected. The content of Li2O in the present invention is 2wt%-6.5wt%, the content of Na2O is 0.5wt%-4wt%, and the content of K2O is 1wt%-4wt%.
[0015] Based on the total mass of the composition for crack resistant glass as 100wt%, the mass fraction of MgO is 1wt%-5wt%, for example, it can be 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] The present invention introduces MgO to improve the glass Na + With Li + Ion exchange performance improves the thermal properties, chemical stability and mechanical strength of the glass. The content of MgO in the present invention is 1wt%-5wt%.
[0017] Taking the total mass of the composition for crack-resistant glass as 100wt%, the mass fraction of Y2O3 is 2wt%-7wt%, for example, it can be 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt% or 7wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] In the present invention, Y2O3 is introduced, and since the radius of Y ions is close to that of Na ions, the internal Na + With Li + The ion exchange rate is beneficial to improve the CS-Na 30 CS-Na 50 At the same time, Y2O3 increases the strain point of the glass, thereby improving the stress relaxation caused by the chemical strengthening process of the glass under long-term or high temperature. The content of Y2O3 in the present invention is 2wt%-7wt%.
[0019] Based on the total mass of the composition for crack-resistant glass being 100wt%, the mass fraction of ZrO2 is 0.5wt%-3.5wt%, for example, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, or 3.5wt%, but is not limited to the listed values, and other values not listed in the numerical range are also applicable. The balance is SiO2.
[0020] The invention introduces ZrO2, which is in the network space and accumulates the surrounding silicon-oxygen tetrahedrons, thereby strengthening the network structure and enhancing the chemical strengthening stress strength, ion exchange speed and depth inside the glass. The content of ZrO2 in the invention is 0.1wt%-0.5wt%.
[0021] The present invention introduces SiO2, which is a component constituting the glass skeleton. SiO2 can be used as the main body of the glass network structure. If the content is low, it is not easy to form glass, the strain point decreases, the expansion coefficient increases, the acid resistance and alkali resistance decrease, and the glass stability is poor. Increasing the SiO2 content can improve the mechanical strength of the glass, reduce the expansion coefficient, and improve the stability of the glass. However, if the content is too high, the high-temperature viscosity of the glass increases, which is not conducive to the melting of the glass. The mass fraction of SiO2 in the composition for crack-resistant glass of the present invention is 61wt%-65wt%.
[0022] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0023] Preferably, the mass fraction of the components in the composition for crack-resistant glass satisfies at least one of the following conditions: (i) 3.91≤A=(SiO2-Al2O3) / (MgO+Y2O3+ZrO2)≤5.87; (ii) 0.38≤B=(Li2O-Na2O) / K2O≤2.5; (iii) 0.27≤C=(Y2O3-Na2O) / (ZrO2+MgO)≤0.76.
[0024] Among them, (i) 3.91≤A=(SiO2-Al2O3) / (MgO+Y2O3+ZrO2)≤5.87, for example, it can be 3.91, 4.0, 4.1, 4.2, 4.3, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8 or 5.87, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0025] The present invention controls 3.91≤A=(SiO2-Al2O3) / (MgO+Y2O3+ZrO2)≤5.87. Within this range, SiO2 is a glass network structure. On the one hand, SiO2 is replaced by [AlO4], which is larger in volume than the silicon-oxygen tetrahedron in the glass network structure, and can increase the ion exchange rate during subsequent glass strengthening and improve the damage resistance of the glass without destroying the overall network structure of the glass. On the other hand, MgO+Y2O3+ZrO2, as a network exosome, has an obvious aggregation effect in the gaps of the glass network and can enhance the glass network structure.
[0026] Preferably, the mass fraction of the composition for crack resistant glass satisfies: (ii) 0.38≤B=(Li2O-Na2O) / K2O≤2.5, for example, it can be 0.38, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4 or 2.5, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0027] The present invention controls 0.38≤B=(Li2O-Na2O) / K2O≤2.5. Within this range, it is beneficial for Li + 、Na + , K + The exchange between them produces sufficient ion exchange depth and improves the chemical strengthening properties of the glass.
[0028] Preferably, the mass fraction of the composition for crack resistant glass satisfies: (iii) 0.27≤C=(Y2O3-Na2O) / (ZrO2+MgO)≤0.76, for example, it can be 0.27, 0.28, 0.29, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75 or 0.76, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0029] The present invention controls 0.27≤C=(Y2O3-Na2O) / (ZrO2+MgO)≤0.76. Within this range, the thermal properties of the glass can be improved, and the strain point of the glass can be increased. The stress relaxation caused by the long-term or high-temperature chemical strengthening process of the first step of chemical strengthening can be improved; at the same time, the second step of chemical strengthening performance can be improved, and the CS-Na 30 CS-Na 50 .
[0030] The present invention optimizes and controls the mass fractions of SiO2, Al2O3, Li2O, Na2O, K2O, MgO, Y2O3 and ZrO2 in the composition for crack-resistant glass, thereby increasing the drop resistance of the crack-resistant glass and improving the drop resistance of the crack-resistant glass.
[0031] In a second aspect, the present invention provides a crack-resistant glass, wherein the crack-resistant glass comprises the composition for crack-resistant glass according to the first aspect.
[0032] The crack-resistant glass provided by the present invention has simple composition, high drop resistance and excellent drop resistance. The thickness of the crack-resistant glass is 0.08mm-1.5mm, and the thinner the crack-resistant glass is, the lighter the glass can be.
[0033] Preferably, the CS-K of the crack-resistant glass is ≥950 MPa, for example, it may be 950 MPa, 955 MPa, 1000 MPa, 1005 MPa, 1010 MPa, 1015 MPa, 1020 MPa, 1025 MPa or 1030 MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] In the present invention, CS-K refers to the compressive stress value of the surface of the strengthened glass, which is mainly achieved by replacing Na ions in the glass with K ions in the strengthening salt.
[0035] Preferably, the CS-Na of the crack-resistant glass 30 ≥160 MPa, for example, it can be 160 MPa, 165 MPa, 170 MPa, 175 MPa, 180 MPa, 185 MPa, 190 MPa, 195 MPa or 200 MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the CS-Na of the crack-resistant glass 50 ≥130MPa, for example, it can be 130MPa, 132MPa, 134MPa, 136MPa, 138MPa, 140MPa, 142MPa, 144MPa, 146MPa, 148MPa, 150MPa, 152MPa, 154MPa, 156MPa, 158MPa or 160MPa, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0037] In the present invention, CS-Na 30 It refers to the compressive stress value at a depth of 30μm after the strengthened glass sample is strengthened by mixed salt. The compressive stress value is mainly due to the exchange of Na ions in the strengthening salt for Li ions in the glass.
[0038] In the present invention, CS-Na 50 It refers to the compressive stress value at a depth of 50μm after the strengthened glass sample is strengthened by mixed salt. The compressive stress value is mainly due to the exchange of Na ions in the strengthening salt for Li ions in the glass.
[0039] Preferably, the DOL-Na of the crack-resistant glass is ≥120 μm, for example, it may be 120 μm, 122 μm, 124 μm, 126 μm, 128 μm, 130 μm, 132 μm, 134 μm, 136 μm, 138 μm, 140 μm, 142 μm, 144 μm, 146 μm, 148 μm or 150 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] Preferably, the DOL-K of the crack-resistant glass is ≥7μm, for example, it can be 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm or 15μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] DOL-Na refers to the exchange depth of Na ions and Li ions in the compressive stress layer of strengthened glass. DOL-K refers to the exchange depth of K ions in the compressive stress layer of strengthened glass.
[0042] Preferably, the drop resistance height of the crack-resistant glass is ≥120 cm, for example, it can be 120 cm, 122 cm, 124 cm, 126 cm, 128 cm, 130 cm, 132 cm, 134 cm, 136 cm, 138 cm, 140 cm, 142 cm, 144 cm, 146 cm, 148 cm, 150 cm, 152 cm, 154 cm, 156 cm, 158 cm or 160 cm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] Preferably, the crack resistance factor of the crack-resistant glass is D=[(CS-Na 30 )-(CS-Na 50 )] / 20μm, D≥1.6MPa·μm -1 , the preferred range is 1.6MPa·μm -1 ≤D≤2MPa·μm -1 , for example, it can be 1.6MPa·μm -1 , 1.7MPa·μm -1 、1.8MPa·μm -1 , 1.9MPa·μm -1 or 2MPa·μm -1 , but not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0044] The inventors have found through research and experiments that when glass falls from a height onto 180-mesh sandpaper, the glass surface will directly contact the raised portion of the 180-mesh sandpaper (30 microns to 50 microns), and the stress value at this position is mainly generated by the exchange of Na ions in the strengthening salt for Li ions in the glass. Therefore, if the strength of the glass surface compressive stress layer is too low or the depth of the surface compressive stress layer is too thin, the stress layer of the glass is easily pierced by the sharp portion of the protrusion, resulting in cracks, causing the glass to break, and the glass has a low drop resistance.
[0045] The present invention proposes a crack resistance factor D, which is obtained by CS-Na 30 CS-Na 50 The stress difference of CS-Na 30 CS-Na 50 The corresponding values are the compressive stress values at the depth of 30μm and 50μm respectively after the tempered glass sample is tempered by mixed salt. The range of D is limited to 1.6MPa·μm -1 The above, within this range, the crack resistance of the crack-resistant glass is excellent, and the preferred range is 1.6MPa·μm -1 ≤D≤2MPa·μm -1 .
[0046] In a third aspect, the present invention provides a method for preparing the crack-resistant glass according to the second aspect, the preparation method comprising the following steps:
[0047] The composition for crack-resistant glass is melted and mixed, and the crack-resistant glass is obtained through clarification, homogenization, molding, annealing and chemical strengthening.
[0048] The present invention adopts a conventional method for preparing crack-resistant glass, wherein the clarifier added during the clarification process includes one or a combination of at least two of sodium chloride, sodium sulfate or cerium oxide, wherein the mass of the composite clarifier is 0.1wt%-0.5wt% of the total mass of the raw materials used for the crack-resistant glass.
[0049] Preferably, the forming method includes any one of a float process, a slot draw process, a casting process or an overflow process.
[0050] Preferably, the step of chemical strengthening comprises:
[0051] S1: Use sodium ion molten salt to strengthen at 430℃-480℃ for 1h-2h; for example, the temperature can be 430℃, 440℃, 450℃, 460℃, 470℃ or 480℃, and the time can be 1h, 1.5h or 2h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0052] S2: Strengthening using potassium ion molten salt at 400°C-430°C for 1h-2h; for example, the temperature may be 400°C, 405°C, 410°C, 415°C, 420°C, 425°C or 430°C, and the time may be 1h, 1.5h or 2h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0053] The sodium ion molten salt used in S1 can be a NaNO3 molten salt with a mass fraction of 100wt%.
[0054] The potassium ion molten salt used in S2 can be a KNO3 molten salt with a mass fraction of 100wt%.
[0055] Preferably, the chemical strengthening further comprises cleaning and drying the crack resistant glass.
[0056] In a fourth aspect, the present invention provides an application of the crack-resistant glass as described in the third aspect, wherein the crack-resistant glass is used in the front cover or back cover of a touch display screen, an electronic intelligent terminal, a photovoltaic power generation device, a car window, a car protective glass, a medicinal glass container or a primary packaging field.
[0057] The crack-resistant glass obtained by the present invention has excellent physical and chemical properties and mechanical properties, and can be applied to the fields of front cover or back cover for touch display screens, electronic intelligent terminals, photovoltaic power generation devices, automobile windows, automobile protective glass, medicinal glass containers or primary packaging, etc.
[0058] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0059] Compared with the prior art, the present invention has at least the following beneficial effects:
[0060] The crack-resistant glass prepared by the crack-resistant glass composition provided by the present invention has a high drop resistance and excellent drop resistance. The crack resistance factor D of the prepared crack-resistant glass is [(CS-Na 30 )-(CS-Na 50 )] / 20μm, the range of D is 1.6MPa·μm -1 Above, the drop resistance height of crack-resistant glass is ≥120cm. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 1 is a graph showing the relationship between the D value of the crack-resistant glass prepared in Examples 1-10 of the present invention and the drop resistance height of 180-mesh sandpaper. DETAILED DESCRIPTION
[0062] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0063] In the following examples and comparative examples, unless otherwise specified, all reagents and consumables were purchased from conventional reagent manufacturers in the field; unless otherwise specified, the experimental methods and technical means used were conventional methods and means in the field.
[0064] Example 1
[0065] The present embodiment provides a composition for crack-resistant glass: based on the total mass of the composition for crack-resistant glass as 100wt%, the mass fraction of Al2O3 is 16wt%, the mass fraction of Li2O is 6.5wt%, the mass fraction of Na2O is 4wt%, the mass fraction of K2O is 1wt%, the mass fraction of MgO is 1wt%, the mass fraction of Y2O3 is 7wt%, the mass fraction of ZrO2 is 3.5wt%, and the remainder is SiO2; and A=(SiO2-Al2O3) / (MgO+Y2O3+ZrO2)=3.91, B=(Li2O-Na2O) / K2O=2.5, C=(Y2O3-Na2O) / (ZrO2+MgO)=0.67, and the content of each component is shown in Table 1 below.
[0066] The method for preparing the crack-resistant glass provided in this embodiment comprises the following steps:
[0067] The glass composition is mixed evenly according to the mass ratio and poured into a platinum-rhodium crucible, and NaNO3 and CeO2 clarifiers are added in a mass ratio of 1:1, and the amount of clarifier added is 0.3wt% of the total amount of raw materials used for the crack-resistant glass, and heated at 1600°C for 5h and mixed evenly. Then the crucible is taken out, and the molten glass liquid is poured into a preheated mold and formed by a casting method. After forming, it is placed in a muffle furnace at 600°C and kept warm for 2h for annealing treatment. After the muffle furnace is cooled to room temperature, it is taken out to obtain a molded crack-resistant glass, and the molded crack-resistant glass is kept warm at a preheating temperature of 380°C for 30 minutes to obtain a pretreated crack-resistant glass.
[0068] The pre-treated crack-resistant glass is chemically strengthened, and the chemical strengthening includes the following steps:
[0069] S1: using 100wt% NaNO3 molten salt at 430℃ for 2h;
[0070] S2: Using 100wt% of KNO3 molten salt, strengthening at 400°C for 1h to obtain the crack-resistant glass.
[0071] Example 2
[0072] This embodiment provides a composition for crack-resistant glass, and the component contents thereof are shown in Table 1; the method for preparing the crack-resistant glass provided in this embodiment comprises the following steps:
[0073] The glass composition is mixed evenly according to the mass ratio and poured into a platinum-rhodium crucible, and NaCl and CeO2 clarifiers are added in a mass ratio of 1:1, and the amount of clarifier added is 0.1wt% of the total amount of the anti-crack glass raw materials. The mixture is heated at 1560°C for 5 hours and mixed evenly. The crucible is then taken out, and the molten glass liquid is poured into a preheated mold and formed by a casting method. After forming, it is placed in a muffle furnace at 550°C and kept warm for 3 hours for annealing. After the muffle furnace is cooled to room temperature, it is taken out to obtain a molded anti-crack glass, and the molded anti-crack glass is kept warm at a preheating temperature of 400°C for 30 minutes to obtain a pretreated anti-crack glass.
[0074] The pre-treated crack-resistant glass is chemically strengthened, and the chemical strengthening includes the following steps:
[0075] S1: using 100wt% NaNO3 molten salt at 430℃ for 2h;
[0076] S2: Using 100wt% of KNO3 molten salt, strengthening at 400°C for 1.5h to obtain the crack-resistant glass.
[0077] Example 3-Example 10
[0078] The contents of the composition for crack-resistant glass in each embodiment are shown in Table 1;
[0079] The method for preparing the crack-resistant glass provided is the same as that of Example 1 except for the chemical strengthening step, wherein the chemical strengthening conditions are shown in Table 2.
[0080] Comparative Example 1
[0081] The content of the glass composition of Comparative Example 1 is shown in Table 1;
[0082] The preparation method of Comparative Example 1 including the chemical strengthening step is the same as that of Example 1.
[0083] Test Method
[0084] The glasses prepared in Examples 1-10 and Comparative Example 1 were tested, and the test results are shown in Table 3 below.
[0085] According to the above glass performance test requirements, the performance of the glass was tested. The CS and DOL of the tempered glass of each embodiment after ion exchange were tested using the Japanese Orihara FSM-6000LE+SLP1000 surface stress meter. Using the birefringence imaging system, polarized light of a specific wavelength passes through the glass with stress gradient, generating a refraction optical path difference, and calculating the relevant stress distribution indicators: CS-K, CS-Na 30 CS-Na 50 , DOL-Na, DOL-K.
[0086] In the present invention, CS-K refers to the compressive stress value of the strengthened glass surface, which is mainly caused by the replacement of Na ions in the glass by K ions in the strengthening salt. DOL-Na refers to the exchange depth of Na ions and Li ions in the compressive stress layer of the strengthened glass. DOL-K refers to the exchange depth of K ions in the compressive stress layer of the strengthened glass.
[0087] CS-Na 30 CS-Na 50 The corresponding values are the compressive stress values at the depth of 30μm and 50μm respectively after the tempered glass sample is tempered by mixed salt. The stress value at this position is mainly generated by the exchange of Na ions in the tempering salt for Li ions in the glass.
[0088] The sandpaper drop performance of the whole machine is measured by a mobile phone controlled drop tester. The specific test conditions are: 180 mesh sandpaper, 195g total weight, 60cm base height, 5cm increment, 1 time per height until it breaks.
[0089] The relationship between the D value of the crack-resistant glass prepared in Examples 1-10 and the drop resistance height of 180-mesh sandpaper is plotted as Figure 1 .
[0090] Table 1
[0091]
[0092]
[0093] Table 2
[0094]
[0095] Table 3
[0096]
[0097]
[0098] The test results show that:
[0099] (1) It can be seen from Examples 1 to 10 that the present invention can greatly improve the drop resistance of the crack-resistant glass by optimizing and regulating the mass fractions of SiO2, Al2O3, Li2O, Na2O, K2O, MgO, Y2O3 and ZrO2 in the crack-resistant glass composition, thereby improving the drop resistance of the crack-resistant glass; the CS-K of the crack-resistant glass is ≥950MPa, and the CS-Na 30 ≥160MPa, CS-Na 50 ≥130MPa, DOL-Na≥120μm, DOL-K≥7μm.
[0100] (2) It can be seen from Examples 1 to 10 that the crack resistance factor D of the crack-resistant glass of the present invention is [(CS-Na 30 )-(CS-Na 50 )] / 20μm, the range of D is 1.6MPa·μm -1 ≤D≤2MPa·μm -1 , the drop resistance height of crack-resistant glass is ≥120cm. Figure 1 It can be clearly seen that the crack resistance factor D of the crack resistant glass is positively correlated with the anti-drop height, that is, the present invention achieves the purpose of improving the performance of the crack resistant glass by regulating and improving the size of the crack resistance factor D.
[0101] (3) By comparing Example 1 with Comparative Example 1, it can be seen that the components of Comparative Example 1 do not fall within the scope of the composition of the present application, parameters A, B and C are not within the scope of the present application, and the crack resistance factor D of Comparative Example 1 is less than 1.6 MPa·μm -1 , the anti-fall performance is significantly reduced, the anti-fall height of 180 mesh sandpaper is reduced, the maximum is only 80cm, and the anti-damage performance is reduced.
[0102] In summary, the present invention improves the drop resistance height of the crack-resistant glass and improves the drop resistance of the crack-resistant glass by optimizing and regulating the mass fractions of SiO2, Al2O3, Li2O, Na2O, K2O, MgO, Y2O3 and ZrO2 in the composition for the crack-resistant glass.
[0103] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A composition for crack-resistant glass, characterized in that: The composition for crack-resistant glass includes SiO2, Al2O3, Li2O, Na2O, K2O, MgO, Y2O3 and ZrO2 in the form of oxides; Taking the total mass of the composition for crack-resistant glass as 100wt%, the mass fraction of Al2O3 is 16wt%-21wt%, the mass fraction of Li2O is 2wt%-6.5wt%, the mass fraction of Na2O is 0.5wt%-4wt%, the mass fraction of K2O is 1wt%-4wt%, the mass fraction of MgO is 1wt%-5wt%, the mass fraction of Y2O3 is 2wt%-7wt%, the mass fraction of ZrO2 is 0.5wt%-3.5wt%, and the balance is SiO2.
2. The composition for crack-resistant glass according to claim 1, characterized in that: The mass fractions of the components in the composition for crack-resistant glass meet at least one of the following conditions: (i)3.91≤A=(SiO2-Al2O3) / (MgO+Y2O3+ZrO2)≤5.87; (ii)0.38≤B=(Li2O-Na2O) / K2O≤2.5; (iii)0.27≤C=(Y2O3-Na2O) / (ZrO2+MgO)≤0.
76.
3. A crack-resistant glass, characterized in that: The crack-resistant glass comprises the composition for crack-resistant glass according to claim 1 or 2.
4. The crack-resistant glass according to claim 3, characterized in that: The CS-K of the crack-resistant glass is ≥950MPa; And / or, the CS-Na of the crack-resistant glass 30 ≥160MPa; And / or, the CS-Na of the crack-resistant glass 50 ≥130MPa; And / or, the DOL-Na of the crack-resistant glass is ≥ 120 μm; And / or, the DOL-K of the crack-resistant glass is ≥7 μm.
5. The crack-resistant glass according to claim 3, characterized in that: The crack resistance factor of the crack-resistant glass is D≥1.6MPa·μm -1 , the preferred range is 1.6MPa·μm -1 ≤D≤2MPa·μm -1 , the crack resistance factor D = [(CS-Na 30 )-(CS-Na 50 )] / 20μm.
6. The crack-resistant glass according to claim 3, characterized in that: The anti-drop height of the crack-resistant glass is ≥120 cm.
7. A method for preparing the crack-resistant glass according to any one of claims 3 to 6, characterized in that: The preparation method comprises the following steps: The crack-resistant glass is obtained by melting and mixing the composition for crack-resistant glass according to claim 1 or 2, and then clarifying, homogenizing, molding, annealing and chemically strengthening.
8. The preparation method according to claim 5, characterized in that: The forming method includes any one of a float process, a slot draw process, a casting process or an overflow process.
9. The preparation method according to claim 7, characterized in that: The chemical strengthening step comprises: S1: Use sodium ion molten salt to strengthen at 430℃-480℃ for 1h-2h; S2: Use potassium ion molten salt to strengthen at 400℃-430℃ for 1h-2h.
10. Use of the crack-resistant glass according to any one of claims 3 to 6, characterized in that: The crack-resistant glass is used in the fields of front cover and / or back cover for touch display screens, electronic intelligent terminals, photovoltaic power generation devices, automobile windows, automobile protective glass, medicinal glass containers or primary packaging.
Citation Information
Patent Citations
Protection glass plate with impact resistance stress property
CN109052934A
Chemical strengthening method of glass, strengthened glass, application and display device
CN111825345A
Glass, tempered glass, preparation method of tempered glass and electronic product
CN112723736A
Tempered glass as well as preparation method and application thereof
CN118108411A
Lithium-aluminum-silicon glass and preparation method thereof
CN118954947A